The Role of Auditor in Promoting the Achievement of Audit Objectives on Banks in Syria A Field Study on Banks of Syria (Damascus University Journal for the economic and Political sciences, 2024)
The study aims to identify the role of auditors in promoting the achievement of the desired objectives of the audit process on Syrian banks, by the legislation related to banking work and international auditing standards. To achieve the objectives of the study, the descriptive and statistical methods were used, and a questionnaire was designed and distributed to (55) auditor working in the field of banks in Syria for the year 2021. In order to analyze the data and extract the results, the statistical packages program SPSS, the one-way analysis of variance test ANOVA, and Student test T for one sample are used. The study concluded that the following audit roles are between the above-middle and the acceptable level. These roles are: the role of audit in enhancing confidence in the effectiveness of the banking supervision system, increasing the truthfulness of financial statements, and providing the users of reports with reasonable assurance about the fairness of the financial statements. Also the study concluded that the following audit roles are within the good level. These roles are: the role of audit as a guarantee of the progress of the bank’s works as well, and the external auditor depends on the work submitted by the internal auditor. The study recommended  that is necessary to concert efforts to raise the level of performance of auditors and to provide them with all that is new in the fields of auditing, accounting and banking.
Keywords: Internal Audit; External Audit; Banking Supervision; Audit Objectives; Syrian Banks